How Does the Dictatorship and Democratic Leadership Styles Affect the Two Main Characters in Lord of the Flies? - Harem Kareem Mahmood (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This paper demonstrates to which extent the dictatorship and democratic leadership styles affect the fates and the decisions of the two main characters in Lord of the Flies namely, Ralph and Jack. It first analyzes the relationship between the psychoanalysis theory and leadership styles in Lord of the Flies. Then, it provides few definitions and viewpoints about the democratic and tyrant leaders. Following that, it relates Ralph’s democratic leadership and the dictatorship rule of Jack to the Freud’s divisions of personality types in his psychoanalytic theory. Finally, it clarifies how Ralph’s Ego and Jack’s Id affect their leadership behaviors, decisions and outcomes on the island.